Utilization of COI Marker for Species Identification and Population Delineation of White Shrimp in the Demak Waters, Indonesia - Jasiel Junior Karosekali; Nenik Kholilah; Almay Atsiil Harits Syam; Subagiyo Subagiyo; Diah Permata Wijayanti; Muggi Bachtiar (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
White shrimp is one of the largest artisanal capture fisheries commodities in Demak. The utilization of these shrimps often overlooks their species category as they are mostly white in appearance. Growing trend of shrimp fishing may affect shrimp management due to population declination to the genetic level since the genetic data are insufficient. Hence, we aim to identify and study the genetic diversity of white shrimp caught in Demak Waters to provide an overview as a reference for fishery improvement project. A random purposive sampling method was used to collect a total of 90 white shrimp specimens from four fishing grounds (Babalan, Gojoyo, Menco, and Seklenting) in the Demak Waters. Specimens were extracted using Chelex 10%, amplified using PCR, and sequenced by the Sanger method based on the mtDNA COI gene. This research revealed the presence of five species of white shrimp: Penaeus merguiensis, Fenneropenaeus penicillatus, Penaeus vannamei, Metapenaeus brevicornis, and Metapenaeus ensis. The genetic diversity studies were continued using the Penaeus merguiensis species only. The results showed 17 haplotypes with a genetic diversity (Hd) of 0.6936 and a nucleotide diversity of 0.00108, which express moderate genetic diversity. Population analysis using Analysis of Molecular Variance (AMOVA) indicated a non-significant difference between the four study populations (panmictic population) with an FST value of 0.00756 (P-value < 0.05). Based on these results, an adequate management of stock is important. For instance, an open-closed season is needed in order to sustain and reduce capture pressure on the white shrimp population in Demak waters.